Clinical Pathology of the Placenta - Turowski, Gitta; Vogel, Martin (De Gruyter, 2019)
This book performs a distinct introduction to the pathology of the placenta and its membranes, abortion material included, with the aim to facilitate and protect the quality of the morphological placental diagnostics by the pathologists. Seven chapters with coloured figures illustrating gross anatomy, development and maturation of the placenta explain the functional morphology in its clinical correlation of single and multiple findings for the pathologists, obstetricians and neonatologists. Moreover, the book contributes to a better understanding of pre- and perinatal investigations, maternal diseases, fetal outcomes and follow up of the newborns, as well as to the prevention of worse outcome in further pregnancies.The atlas intends to stimulate the interest for perinatal pathology and to contribute to a better interdisciplinary understanding of pathologists and clinicians, midwives and nurses.